Changes in the management and comorbidities of acromegaly over three decades: the French Acromegaly Registry. Issue 5 (May 2017) - Maione, Luigi; Brue, Thierry; Beckers, Albert; Delemer, Brigitte; Petrossians, Patrick; Borson-Chazot, Françoise; Chabre, Olivier; François, Patrick; Bertherat, Jérôme; Cortet-Rudelli, Christine; Chanson, Philippe; ,
Abstract : Context: Acromegaly is a rare disease associated with chronic multisystem complications. National registries have been created in several countries. Design: The French Registry contains data on acromegaly epidemiology, management and comorbidities recorded over more than three decades, retrospectively until 1999 and prospectively from 1999 to 2012. Results: Data could be analyzed for 999 of the 1034 patients included in the registry (46% males). Disease control, defined as IGF-I normalization (adjusted for age and sex), was achieved in 75% of patients at the last follow-up visit. Half the patients with uncontrolled disease had IGF-I levels below 1.5 times the upper limit of normal (ULN). The proportion of patients with surgically cured disease did not change markedly over time, whereas the proportion of patients with uncontrolled disease fell and the proportion of patients with medically controlled disease rose. Cardiovascular, metabolic, respiratory and rheumatologic comorbidities and their outcomes were recorded for most patients, and no noteworthy overall deterioration was noted over time. Cancer occurred in 10% of patients, for a standardized incidence ratio of 1.34 (95% CI: 0.94–1.87) in men and 1.24 (0.77–1.73) in women. Forty-one patients died during follow-up, for a standardized mortality ratio of 1.05 (0.70–1.42). Most deaths were due to cancer. Conclusions: The majority of patients with acromegaly now have successful disease control thanks to the multistep management. The incidence of comorbidities following diagnosis of acromegaly is very low. Life expectancy is now close to that of the general population, probably owing to better management of the GH/IGF-I excess and comorbidities.